Efektifitas Asesmen Pembelajaran Berbasis Quiziz Pada Mata.Pelajaran.Kelas VII.di SMP Negeri 2 Padang - Hilahi, Wahyu; Yeni J, Fetri (Jurnal Family Education, 2023)
The purpose.of .his study.is to.determine the efficacy of the application  Quiziz-based learning assessments which are useful for improving student learning outcomes, and can assist teachers in carrying out evaluations easily. Where students tend to be inactive, less interested and less interested during learning activities. This is because the assessment carried out is not interesting so that students are not challenged to take the exam The type of study used is a quantitative approach in a quasi-experimental form. The study was conducted on 25 of her students, including all students in Class VII of SMP Negri 2 Padang. A total of 229 persons consisted of samples from 8 classes and classes VII.5 (control class) and VII.2 (experimental class). The data analysis technique uses the t-test (t-test), which has previously been tested for normality and homogeneity. The results show that tcount = 33.430 is greater than ttable = 1.678 using the tcount test formula to test the hypothesis. The average learning outcome scores of students using quiz-based learning assessment (experimental teaching) are higher than the average learning outcome scores of students who did not use quiz-based learning assessment. This is consistent with students' average learning outcomes of 84.78 using quiz-based learning assessment, compared to 78.77 without quiz-based assessment.